Identification of bedrock types beneath the ice sheet by radio echo sounding in the bare ice field near the Yamato Mountains, Antarctica - Ohmae, Hirokazu; Nishio, Fumihiko; Katsushima, Takayoshi; Ishikawa, Masao; Takahashi, Shuhei (1984)
P(論文) From December 1982 to January 1983 an oversnow traverse party of the 23rd Japanese Antarctic Research Expedition carried out radio echo sounding of a bare ice area near the Yamato Mountains in Antarctica. On the basis of photographs of A-scope recorder which were taken every 1km along the traverse routes, the reflection intensity of the radio echo signals from the ice/bedrock interface was calculated by correcting the effect of the attenuation loss of electromagnetic waves within the ice sheet. Rock specimens collected from Massif A of the Yamato Mountains, the Minami-Yamato Nunataks and the nearby moraine field, and dielectric constants of the rocks were measured in a frequency range from 3 to 50MHz. According to the measurements, the values of dielectric constant of the rock samples varied from 2 to 5. To identify bedrock types beneath the ice sheet in the bare ice area, the reflection intensity of the bedrock is compared with the echo strength calculated from the measured dielectric constant of rock samples. It is found that the bedrock is granitic gneiss in the region near Massif A of the Yamato Mountains, and there are a few areas along the traverse route where the bedrock gives a strong echo between -10 and -20dB. departmental bulletin paper